Mainstreaming the needs of migrant children and sending communities into the rural schools development agenda in Kyrgyzstan - Murzakulova, A.; Abdoubaetova, A. (University of London, 2022)
Many studies indicate that labor migration is the main economic survival strategy for all population groups in Kyrgyzstan, but especially young people. Migration affects rural schools in several ways. Young people are not interested in fully completing their secondary education, and after the 9th grade, many drop out of school and start looking for jobs. This problem is compounded by the shortage of school teachers in the country. According to the Ministry of Education and Science of the Kyrgyz Republic, teaching vacancies in subjects such as computer science, English, biology, chemistry, mathematics and physical education have not been filled for years in many schools. Recent university graduates are not interested in filling these vacancies as labor migration offers a more favorable way of entering the labor market. This migration of the working age population can, however, have a negative impact on left-behind children, worsening their academic performance. National Assessment of the Educational Achievements for grad school students (NOODU) data show that students’ performance at schools differs markedly between children whose parents are labour migrants outside of the country and their peers whose parents remain with them. The former often have the worst performances in schools. This is mostly because left behind children, mostly teens, have to fill the labour shortage in the household. The multidimensional impacts of labor mobility are therefore closely intertwined and reflected in problems felt within the school system (lack of teachers and poor academic performance of migrant children). This can cause long-term negative impacts on education. However, despite the scale of labor migration, very little has been done to understand how rural schools cope with these challenges. This policy brief aims to raise stakeholder awareness of the impact of labor migration on the institution of secondary education in rural communities with active migration outflows, and offers key recommendations for further actions and interventions.